2017
DOI: 10.1016/j.ijid.2017.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Sustained pediatric antimicrobial stewardship program with consultation to infectious diseases reduced carbapenem resistance and infection-related mortality

Abstract: A sustained ASP with additional consultation with the infectious disease service reduced carbapenem use and resistance in P. aeruginosa, leading to favorable outcomes in terms of length of hospitalization and infection-related mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 23 publications
3
59
1
3
Order By: Relevance
“…None of the patients was treated with carbapenem as definitive therapy. The antimicrobial stewardship program at the present hospital restricts the use of broad‐spectrum antimicrobial agents and encourages the use of narrower spectrum antimicrobial agents whenever possible . Another implication of this study, however, is that carbapenem use may be spared in non‐severe cases of pediatric pyelonephritis caused by ESBL‐producing Enterobacteriaceae.…”
Section: Discussionmentioning
confidence: 89%
“…None of the patients was treated with carbapenem as definitive therapy. The antimicrobial stewardship program at the present hospital restricts the use of broad‐spectrum antimicrobial agents and encourages the use of narrower spectrum antimicrobial agents whenever possible . Another implication of this study, however, is that carbapenem use may be spared in non‐severe cases of pediatric pyelonephritis caused by ESBL‐producing Enterobacteriaceae.…”
Section: Discussionmentioning
confidence: 89%
“…Implementation of a prospective audit with intervention and feedback is useful for solving these problems. Reports have shown that implementing a pre‐authorisation and prospective audit with intervention and feedback reduces the infection‐related mortality rate and treatment duration, and improves the clinical response in patients receiving carbapenem. However, it is still unclear whether or not a prospective audit with intervention and feedback without carbapenem restriction improves clinical outcomes in patients receiving carbapenem injection.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of 30-d re-infection was significantly lower (13.4% vs 3.2%, P < 0.001; Table 2), and the re-infection-free survival was significantly longer in the intervention group (HR, 0.35; 95% CI, 0.18-0.68; P = 0.002; Figure 2B). No significant differences were noted in the treatment duration (7 [5][6][7][8][9][10]…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 2 more Smart Citations